2013
DOI: 10.1073/pnas.1221214110
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate intrinsic diversity enhances neural population coding

Abstract: Cell-to-cell variability in molecular, genetic, and physiological features is increasingly recognized as a critical feature of complex biological systems, including the brain. Although such variability has potential advantages in robustness and reliability, how and why biological circuits assemble heterogeneous cells into functional groups is poorly understood. Here, we develop analytic approaches toward answering how neuron-level variation in intrinsic biophysical properties of olfactory bulb mitral cells inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
125
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 45 publications
18
125
1
Order By: Relevance
“…Furthermore, under more realistic scenarios using inputs that were highly similar but not identical, heterogeneity among the neuronal firing responses still improved the neural coding of a common signal. Studies in the olfactory bulb have shown similar effects that we show here, such that the diversity of the intrinsic properties of mitral cells receiving common inputs improved coding by reducing redundancy and generating heterogeneity in the temporal patterning of activity (Padmanabhan and Urban 2010; Tripathy et al 2013). Intrinsic biophysical heterogeneity may thus be a common mechanism for improved sensory coding.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Furthermore, under more realistic scenarios using inputs that were highly similar but not identical, heterogeneity among the neuronal firing responses still improved the neural coding of a common signal. Studies in the olfactory bulb have shown similar effects that we show here, such that the diversity of the intrinsic properties of mitral cells receiving common inputs improved coding by reducing redundancy and generating heterogeneity in the temporal patterning of activity (Padmanabhan and Urban 2010; Tripathy et al 2013). Intrinsic biophysical heterogeneity may thus be a common mechanism for improved sensory coding.…”
Section: Discussionsupporting
confidence: 71%
“…Spiking activity by individual neurons could account for ϳ22% of the stimulus variance, with high coherence with the stimulus in the frequency range of 10 -80 Hz. Individual neurons had an average information rate of ϳ2.5 bits/spike, comparable to estimates of coding efficiency in other peripheral, auditory or sensory areas (Bialek et al 1991;Borst and Theunissen 1999;Butts et al 2010;Rieke et al 1997;Tripathy et al 2013). There was a strong positive correlation between a neuron's reliability and how much information each spike carried: the more reliable the firing, the more informative was each spike.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The observed behaviour emerges as a statistical average of the whole cell ensemble that may however show a significant diversity at the single-cell level [2]. The diversity of the basic units in complex biological systems, such as a biomembrane [3,4] and the brain [5,6], increases functionality and reliability. In particular, a certain level of neural response diversity can be beneficial to coding and decoding processes [6,7].…”
Section: Introductionmentioning
confidence: 99%